Implementation of the Student Scholarship Program as Human Resource Development for Inmates at Madiun Class I Penitentiary - Adiyatma, Herlambang Prasista; Kurniawan, Andi (Social Sciences Journal, 2025)
Fulfillment of educational rights is one of the efforts to improve the quality of prisoners in prisons. There are three categories of educational programs in prisons, namely formal, non-formal, and informal education. However, most prisons only implement non-formal and informal education, while formal education is limited to the A and B package catch-up programs. Therefore, it is necessary to fulfill educational rights to improve the quality of prisoners in prisons by providing undergraduate education to prisoners. The problem in this study concerns the implementation and obstacles in the student scholarship program as a development of human resources for prisoners in Class I Madiun Prison. This study aims to determine the implementation and obstacles of the student scholarship program as a development of human resources for prisoners. The theory used in this study is the theory of policy implementation. This study uses a qualitative method. The results of this study are that there are already standards and policy targets; there are already potential resources and there is an assessment in the selection of prisoners; there is good communication and commitment between the Class I Madiun Prison, the Madiun City Government, and the Open University; there are implementing agents who have good relationships; positive responses from prisoners to attend lectures; free tuition for prisoners, prisons that are improving to provide the best service and scholarship programs that are flagship programs and support from the Madiun City Government. In addition, the obstacles experienced are the lack of information about standards and policy targets; prisoners' hesitation to follow scholarships; forums and supervision that are still lacking; officers who are not ready at the beginning of lectures; lecturers who feel awkward and afraid when teaching; prisoners find it difficult to receive material; limited lecture facilities and infrastructure; there is no clarity if prisoners get integration rights.